EFEITO NEUROPROTETOR DE NANOCÁPSULAS CONTENDO MELOXICAM EM UM MODELO DA DOENÇA DE ALZHEIMER INDUZIDO PELO PEPTÍDEO β- AMILOIDE EM CAMUNDONGOS - Ianiski, Francine Rodrigues (2011)
Alzheimer's disease (AD) is a chronic neurodegenerative pathologic process associated with aging. This disease causes cognition deterioration and memory loss. The formation of senile plaques containing amyloid-β peptide (aβ) is the main characteristic of this disease. Also, AD related with the inflammation and oxidative stress. The lack of drugs used in the prevention and treatment of AD has stimulated the search for new agents that may represent a novel therapeutic alternative. In the present study, we investigated the beneficial effect of meloxicam-loaded nanocapsules in a model of AD induced by intracerebroventricular (i.c.v.) injection of aβ peptide (fragment 25-35) in mice, comparing the effect with free meloxicam. Mice were divided into six groups: (I) control, (II) aβ, (III) Nano, (IV) Free, (V) Nano + aβ and (VI) Free + aβ. Mice were treated with meloxicam-loaded nanocapsules (5 mg/kg, by gavage), free-meloxicam (5 mg/kg, by gavage) or blank nanocapsules. Thirty minutes after treatments, aβ (3 nmol) or filtered water were i.c.v. injected (day 1). Learning and memory were assessed with the Morris water-maze and step-down-type passive-avoidance tasks at the days 4–7 and 7–8 after the aβ injection, respectively. At the end of the experimental protocol, animals were died and brains were removed for determination of reactive species (RS) and non-protein thiols (NPSH) levels, and superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR), glutathione S-transferase (GST) activities. The results demonstrated that aβ injection caused learning and memory deficits in mice, which were verified using the Morris water-maze and step-down-type passiveavoidance tasks. Furthermore, this study showed that oxidative stress was increased in mice that received aβ. The most important findings of the present study was that meloxicam-loaded nanocapsules protected the learning and memory impairments induced by aβ. Moreover, meloxicam-loaded nanocapsules also protected against the increase of oxidative stress. However, free-meloxicam did not have protective effect. All these findings support the beneficial role of meloxicam-loaded nanocapsules in a model of AD induced by aβ. We can suggest that nanocapsules favor the passage of meloxicam through the blood-brain barrier and entry of the drug in the central nervous system.